2022
DOI: 10.1021/acs.jpcc.2c03226
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Zinc 2,11,20,29-Tetra-tert-butyl-2,3-Naphthalocyanine: Aggregation-Induced S2 Emission and Rapid Intersystem Crossing in the Solid State

Abstract: Aggregation can dramatically alter the photophysics of organic chromophores by modulating their electronic properties. Zinc 2,11,20, in thin films emits primarily from its second excited singlet state (S 2 ), while t-Bu-ZnNc in solution obeys the well-known Kasha rule and emits from S 1 . This behavior most likely results from the hindered motion of the t-butyl groups in the rigid, closely packed thin films. This is corroborated by the observation of enhanced S 2 emission in low-temperature glassy solutions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…Overall, the values are indicative of a high production of singlet oxygen, confirming the priority role of the ISC in the decay of the excited PS to the fundamental electronic level. Even if the differences are not significant, a slight tendency for Zn-porphyrins to show a greater Φ Δ is observed; on average, this is in agreement with the results in the literature, where it is reported that the coordination with zinc ion favors the ISC process [ 51 ]. Regarding the pendants, the PSs with the two longest alkyl chains (C8 and C12) show the highest 1 O 2 production in the two series.…”
Section: Resultssupporting
confidence: 90%
“…Overall, the values are indicative of a high production of singlet oxygen, confirming the priority role of the ISC in the decay of the excited PS to the fundamental electronic level. Even if the differences are not significant, a slight tendency for Zn-porphyrins to show a greater Φ Δ is observed; on average, this is in agreement with the results in the literature, where it is reported that the coordination with zinc ion favors the ISC process [ 51 ]. Regarding the pendants, the PSs with the two longest alkyl chains (C8 and C12) show the highest 1 O 2 production in the two series.…”
Section: Resultssupporting
confidence: 90%